Star formation rates and efficiencies in the Galactic Centre - Barnes, Ashley Thomas; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2017)
The inner few hundred parsecs of the Milky Way harbours gas densities, pressures, velocity dispersions, an interstellar radiation field and a cosmic ray ionization rate orders of magnitude higher than the disc; akin to the environment found in star-forming galaxies at high redshift. Previous studies have shown that this region is forming stars at a rate per unit mass of dense gas which is at least an order of magnitude lower than in the disc, potentially violating theoretical predictions. We show that all observational star formation rate diagnostics - both direct counting of young stellar objects and integrated light measurements - are in agreement within a factor two, hence the low star formation rate (SFR) is not the result of the systematic uncertainties that affect any one method. As these methods trace the star formation over different time-scales, from 0.1 to 5 Myr, we conclude that the SFR has been constant to within a factor of a few within this time period. We investigate the progression of star formation within gravitationally bound clouds on ∼parsec scales and find 1-4 per cent of the cloud masses are converted into stars per free-fall time, consistent with a subset of the considered ‘volumetric’ star formation models. However, discriminating between these models is obstructed by the current uncertainties on the input observables and, most importantly and urgently, by their dependence on ill-constrained free parameters. The lack of empirical constraints on these parameters therefore represents a key challenge in the further verification or falsification of current star formation theories.